2022
DOI: 10.1097/ftd.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term High-Fat Diet Alters Acetaminophen Metabolism in Healthy Individuals

Abstract: Background: Acetaminophen is metabolized through a nontoxic sulfation and glucuronidation pathway and toxic oxidation pathway (via CYP2E1 and CYP1A2). A short-term high-fat diet induces alterations in the steatotic liver and may alter hepatic drug enzyme activity. In the case of acetaminophen, these alterations may result in an increased risk of hepatotoxicity. Therefore, this study was conducted to assess the effect of a 3-day hypercaloric high-fat diet on the plasma levels of acetaminophen metabolites.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Accumulation of some fatty acids such as palmitic acid (C16:0) and stearic acid (C18:0) might play a role [ 74 , 98 , 99 ]. In keeping with the role of some fatty acids or lipids, a recent interventional study in healthy individuals showed that a short-term regular diet supplemented with whipped cream induced hepatic steatosis and significantly enhanced CYP2E1 activity [ 100 ]. Other mechanisms might involve hyperleptinemia, hyperglucagonemia and insulin resistance [ 10 , 25 , 82 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…Accumulation of some fatty acids such as palmitic acid (C16:0) and stearic acid (C18:0) might play a role [ 74 , 98 , 99 ]. In keeping with the role of some fatty acids or lipids, a recent interventional study in healthy individuals showed that a short-term regular diet supplemented with whipped cream induced hepatic steatosis and significantly enhanced CYP2E1 activity [ 100 ]. Other mechanisms might involve hyperleptinemia, hyperglucagonemia and insulin resistance [ 10 , 25 , 82 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…Quick snacks and fast foods enriched with simple sugars, fats, and flavorings create the impression of satiety and food satisfaction. Although there is an assurance that only a prolonged high-fat/highcarbohydrate diet leading to obesity and other metabolic diseases can cause sustainable changes in host and gut microbiota metabolism, in recent years, additional evidence of the crucial influence of a short-term high-fat diet on the gut microbiota and host metabolism has appeared 17,[26][27][28] . It is known that diet-induced changes in the gut microbiome occur rapidly (within days) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Quick snacks and fast foods enriched with simple sugars, fats, and flavorings create the impression of satiety and food satisfaction. Although there is an assurance that only a prolonged high-fat/high-carbohydrate diet leading to obesity and other metabolic diseases can cause sustainable changes in host and gut microbiota metabolism, in recent years, additional evidence of the crucial influence of a short-term high-fat diet on the gut microbiota and host metabolism has appeared [ 17 , 23 , 24 , 25 ]. It is known that diet-induced changes in the gut microbiome occur rapidly (within days) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%